IMPROVED NUMERICAL MODEL OF THE ARTERIAL WALL APPLIED FOR SIMULATIONS OF STENT DEPLOYMENT WITHIN PATIENT-SPECIFIC CORONARY ARTERIES - Djukic, Tijana; Saveljic, Igor; Pelosi, Gualtiero; Parodi, Oberdan; Filipovic, Nenad (Journal of Applied Engineering Science, 2020)
Arterial stenosis is the obstruction of normal blood flow that is caused by atherosclerosis. One of the endovascular treatment procedures in this case is the implantation of a stent to restore the blood flow. This study presented an improved numerical model that can precisely simulate the deformation of human arterial wall in coronary arteries, during the stent deployment process. The new model considered the arterial wall as an incompressible, isotropic and hyperelastic material. The material coefficients were defined according to experimental values presented in literature. The accuracy of the numerical model was investigated by comparing the results with follow up data obtained in clinical examination. The small relative and standard deviation error prove that this numerical model can be used to assist clinicians in decision making and treatment planning with reliable predictions of the outcome of the stent deployment procedure.
Keywords: stent expansion; prediction of shape; deformation; hyperelastic material model; stress-strain relationship; finite element method